Students’ acceptance of mobile-based assessment - Nur Adillawati Kosim Saputri; Ade Gafar Abdullah; Dadang Lukman Hakim (Momentum: Physics Education Journal, 2021)
The effective development of a Mobile-Based Assessment (MBA) depends on students’ acceptance. The aim of this paper was to examine the determinant factor of students’ behavioral intention to use mobile-based assessment. Data were collected from 105 second grade students of a vocational high school through an online survey questionnaire. Partial Least Squares (PLS) was used to test the measurement and the structural model. Results showed Perceived Ease of Use as the strongest direct predictor of Behavioral Intention to Use, followed by Perceived Usefulness. Content and Mobile Self-Efficacy only has an indirect effect. These four variables explain 51.3 percent of the variance of Behavioral Intention to Use.